2010
DOI: 10.1029/2009je003500
|View full text |Cite
|
Sign up to set email alerts
|

Radiative transfer modeling of near‐infrared reflectance of lunar highland and mare soils

Abstract: [1] With near-infrared hyperspectral data sets returned from KAGUYA/SELENE and Chandrayaan-1's Moon Mineralogic Mapper (M 3 ), accurate evaluation and interpretation of lunar data sets with higher spectral resolution has never been more critical. Here we test a new radiative transfer spectral modeling algorithm to determine composition from hyperspectral reflectance spectra of lunar soils. Data for 19 lunar mare and highland soil samples previously characterized by the Lunar Soil Characterization Consortium ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…; Cahill et al. , ; Li and Li ). The significant difference between the two models is in how they approximate different scattering processes for photons.…”
Section: Introductionmentioning
confidence: 97%
“…; Cahill et al. , ; Li and Li ). The significant difference between the two models is in how they approximate different scattering processes for photons.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, the Fe 2 + absorption is affected by amorphization due to shock [Adams et al, 1979], resulting in a weaker 1.2-1.3 μm band and a shift in the main absorption feature toward 1 μm [Pieters, 1996;Johnson and Hörz, 2003]. Although estimates of plagioclase, pyroxene, and olivine abundances can be derived from VNIR spectra through nonlinear spectral unmixing (typically using the Hapke [1981, 1993]-or Shkuratov et al [1999-based implementations of radiative transfer theory [e.g., Tompkins and Pieters, 1999;Cahill et al, 2010]), Cahill et al [2010] found that plagioclase abundance is typically underestimated, while no single phase is correspondingly overestimated. Yamamoto et al [2010] Supporting Online Material (SOM) fit SP spectra (0.5-2.6 μm) for 6 out of 33 total regional detections with a radiative transfer-based intimate mixture model [Denevi et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…This method allows a planetary spectrum to be modeled on the basis of optical properties determined for suspected constituents and assumptions regarding the physical state of the surface. Initial applications of radiative transfer theory, based upon work from Bruce Hapke [e.g., Hapke, 1981, to planetary spectra yield encouraging results [e.g., Harker et al, 2002;Birlan et al, 2007;Cahill et al, 2010;Emery et al, 2011]. The accuracy of such models is limited by the quality of the inputs (i.e., optical constants).…”
Section: Introductionmentioning
confidence: 99%